The Oxford movement Europe and the wider world 1830-1930 - Brown, Stewart J. (Stewart Jay), 1951-; Nockles, Peter Benedict (Cambridge : Cambridge University Press, 2012)
"The Oxford Movement transformed the nineteenth-century Church of England with a renewed conception of itself as a spiritual body. Initiated in the early 1830s by members of the University of Oxford, it was a response to threats to the established church posed by British Dissenters, Irish Catholics, Whig and Radical politicians, and the predominant evangelical ethos - what Newman called 'the religion of the day'. The Tractarians believed they were not simply addressing difficulties within their national Church, but recovering universal principles of the Christian faith. To what extent were their beliefs and ideals communicated globally? Was missionary activity the product of the movement's distinctive principles? Did their understanding of the Church promote, or inhibit, closer relations among the churches of the global Anglican Communion? This volume addresses these questions and more with a series of case studies involving Europe and the English-speaking world during the first century of the Movement"--
Machine generated contents note: Notes on contributors; Abbreviations; Introduction Stewart J. Brown and Peter Nockles; Prelude; 1. The Oxford Movement in an Oxford college: Oriel as the cradle of Tractarianism Peter Nockles; Part I. Beyond England: The Oxford Movement in Britain, the Empire and the United States: 2. Isaac Williams and Welsh Tractarian theology John Boneham; 3. Scotland and the Oxford Movement Stewart J. Brown; 4. The Oxford Movement and the British Empire: Newman, Manning and the 1841 Jerusalem Bishopric Rowan Strong; 5. The Australian Bishops and the Oxford Movement Austin Cooper; 6. Anglo-Catholicism in Australia, c.1860-1960 David Hilliard; 7. The Oxford Movement and the United States Peter Nockles; Part II. The Oxford Movement and Continental Europe: 8. Europe and the Oxford Movement Geoffrey Rowell; 9. Pusey, Tholuck and the reception of the Oxford Movement in Germany Albrecht Geck; 10. The Oxford Movement: reception and perception in Catholic circles in nineteenth-century Belgium Jan De Maeyer and Karel Strobbe; 11. 'Separated brethren': French Catholics and the Oxford Movement Jeremy Morris; 12. The Oxford Movement, Jerusalem and the Eastern question Mark Chapman; 13. Ignaz von Döllinger and the Anglicans Angela Berlis; 14. Anglicans, Old Catholics and Reformed Catholics in late nineteenth-century Europe Nigel Yates; Index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Oxford movement; Church of England -- History -- 19th century; RELIGION / History; RELIGION / Christianity / Anglican; Electronic books